Effects of hexahydrocurcumin in combination with 5-fuorouracil on dimethylhydrazine-induced colon cancer in rats - Srimuangwong K. (WJG Press, 2015)
AIM: To investigate the effects of hexahydrocurcumin (HHC), and its combination with 5-fluorouracil (5-FU) on dimethylhydrazine (DMH)-induced colon cancer in rats. METHODS: Male Wistar rats weighing 100-120 g were used as subject models. Aberrant crypt foci (ACF), early preneoplastic lesions of colon cancer, were induced by subcutaneous injection of DHM (40 mg/kg) twice a week for two weeks. After the first DMH injection, rats were treated daily with vehicle (n = 12), curcumin (CUR) (50 mg/kg) (n = 12), HHC (50 mg/kg) orally (n = 12), and treated weekly with an intraperitoneal injec- tion of 5-FU (50 mg/kg) (n = 12), or a combination of 5-FU plus CUR (n = 12) and HHC (n = 12) at the same dosage(s) for 16 wk. The total number of ACF and large ACF were assessed. Cyclooxygenase (COX)-1 and COX-2 expression were detected by immunohistochemistry in colon tissues. The quantitative data of both COX-1 and COX-2 expression were presented as the percentage of number of positive-stained cells to the total number of cells counted. Apoptotic cells in colon tissues were also visualized using the dUTP-biotin nick end labeling method. Apoptotic index (AI) was determined as the percentage of labeled nuclei with respect to the total number of nuclei counted. RESULTS: The total number of ACF was highest in the DMH-vehicle group (1558.20 ± 17.37), however, the number of ACF was significantly reduced by all treat- ments, 5-FU (1231.20 ± 25.62 vs 1558.20 ± 17.37, P < 0.001), CUR (1284.20 ± 25.47 vs 1558.20 ± 17.37, P < 0.001), HHC (1086.80 ± 53.47 vs 1558.20 ± 17.37, P < 0.001), DMH-5-FU + CUR (880.20 ± 13.67 vs 1558.20 ± 17.37, P < 0.001) and DMH-5-FU + HHC (665.80 ± 16.64 vs 1558.20 ± 17.37, P < 0.001). Interestingly, the total number of ACF in the combined treatment groups, the DMH-5-FU + CUR group (880.20 ± 13.67 vs 1231.20 ± 25.62, P < 0.001; 880.20 ± 13.67 vs 1284.20 ± 25.47, P < 0.001) and the DMH-5-FU + HHC group (665.80 ± 16.64 vs 1231.20 ± 25.62, P < 0.001; 665.80 ± 16.64 vs 1086.80 ± 53.47, P < 0.001) were signifcantly reduced as compared to 5-FU or each treatment alone. Large ACF were also signifcantly re- duced in all treatment groups, 5-FU (111.00 ± 7.88 vs 262.20 ± 10.18, P < 0.001), CUR (178.00 ± 7.33 vs 262.20 ± 10.18, P < 0.001), HHC (186.60 ± 21.51 vs 262.20 ± 10.18, P < 0.001), DMH-5-FU + CUR (122.00 ± 5.94 vs 262.20 ± 10.18, P < 0.001) and DMH-5-FU + HHC (119.00 ± 17.92 vs 262.20 ± 10.18, P < 0.001) when compared to the vehicle group. Furthermore, in the DMH-5-FU + CUR and DMH-5-FU + HHC groups the formation of large ACF was significantly reduced when compared to CUR (122.00 ± 5.94 vs 178.00 ± 7.33, P < 0.005) or HHC treatment alone (119.00 ± 17.92 vs 186.60 ± 21.51, P < 0.001), however, this reduction was not statistically different to 5-FU mono- therapy (122.00 ± 5.94 vs 111.00 ± 7.88, P = 0.217; 119.00 ± 17.92 vs 111.00 ± 7.88, P = 0.619, respectively). The levels of COX-1 protein after all treatments were not different from normal rats. A marked increase in the expression of COX-2 protein was observed in the DMH-vehicle group. Over-expression of COX-2 was not significantly decreased by 5-FU treatment alone (95.79 ± 1.60 vs 100 ± 0.00, P = 0.198). However, over-expression of COX-2 was signifcantly suppressed by CUR (77.52 ± 1.68 vs 100 ± 0.00, P < 0.001), HHC (71.33 ± 3.01 vs 100 ± 0.00, P < 0.001), 5-FU + CUR (76.25 ± 3.32 vs 100 ± 0.00, P < 0.001) and 5-FU + HHC (68.48 ± 2.24 vs 100 ± 0.00, P < 0.001) in the treated groups compared to the vehicle group. More- over, CUR (77.52 ± 1.68 vs 95.79 ± 1.60, P < 0.001), HHC (71.33 ± 3.01 vs 95.79 ± 1.60, P < 0.001), 5-FU + CUR treatments (76.25 ± 3.32 vs 95.79 ± 1.60, P < 0.001) and 5-FU + HHC (68.48 ± 2.24 vs 95.79 ± 1.60, P < 0.001) markedly decreased COX-2 protein expression more than 5-FU alone. Furthermore, the AI in all treated groups, 5-FU (38.86 ± 4.73 vs 23.56 ± 2.12, P = 0.038), CUR (41.78 ± 6.92 vs 23.56 ± 2.12, P < 0.001), HHC (41.06 ± 4.81 vs 23.56 ± 2.12, P < 0.001), 5-FU + CUR (49.05 ± 6.75 vs 23.56 ± 2.12, P < 0.001) and 5-FU + HHC (53.69 ± 8.59 vs 23.56 ± 2.12, P < 0.001) significantly increased when compared to the DMH-vehicle group. However, the AI in the combination treatments, 5-FU + CUR (49.05 ± 6.75 vs 41.78 ± 6.92, P = 0.192; 49.05 ± 6.75 vs 38.86 ± 4.73, P = 0.771) and 5-FU + HHC (53.69 ± 8.59 vs 41.06 ± 4.81, P = 0.379; 53.69 ± 8.59 vs 38.86 ± 4.73, P = 0.245) did not reach significant levels as compared with each treatment alone and 5-FU monotherapy, respectively. CONCLUSION: The combined effects of HHC with 5-FU exhibit a synergistic inhibition by decreasing ACF formation mediated by down-regulation of COX-2 expression. © 2012 Baishideng. All rights reserved.